2020
DOI: 10.3390/en13020491
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced Biogas Production of Cassava Wastewater Using Zeolite and Biochar Additives and Manure Co-Digestion

Abstract: Currently, there are challenges with proper disposal of cassava processing wastewater, and a need for sustainable energy in the cassava industry. This study investigated the impact of co-digestion of cassava wastewater (CW) with livestock manure (poultry litter (PL) and dairy manure (DM)), and porous adsorbents (biochar (B-Char) and zeolite (ZEO)) on energy production and treatment efficiency. Batch anaerobic digestion experiments were conducted, with 16 treatments of CW combined with manure and/or porous adso… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 27 publications
(16 citation statements)
references
References 38 publications
0
9
0
Order By: Relevance
“…These strategies may aid in improving the performance of high-solid digestion and solid-phase reactors, given the high tendency of accumulating an excessive amount of inhibitors because of the lower volume of the diluting agent. Petracchini et al [102] reported the performance of HSAD of food waste and cow manure when adding natural zeolite to the reactor, obtaining biogas yields of 680-920 mL/g VS. Adsorbents have the capacity of reducing inhibitory levels of ammonia and total VFA concentration, thus allowing stable digestion to proceed [103,104]. Cuetos et al [105] demonstrated this better performance when evaluating the digestion of poultry blood.…”
Section: Increasing Reactor Productivity By the Increase In Solid Content And Temperaturementioning
confidence: 99%
“…These strategies may aid in improving the performance of high-solid digestion and solid-phase reactors, given the high tendency of accumulating an excessive amount of inhibitors because of the lower volume of the diluting agent. Petracchini et al [102] reported the performance of HSAD of food waste and cow manure when adding natural zeolite to the reactor, obtaining biogas yields of 680-920 mL/g VS. Adsorbents have the capacity of reducing inhibitory levels of ammonia and total VFA concentration, thus allowing stable digestion to proceed [103,104]. Cuetos et al [105] demonstrated this better performance when evaluating the digestion of poultry blood.…”
Section: Increasing Reactor Productivity By the Increase In Solid Content And Temperaturementioning
confidence: 99%
“…The addition of adsorbents and carbon conductive materials to anaerobic reactors has been evaluated with success to decrease the impact of inhibitory compounds [87,88]. Adding this type of supplement to digestion allows for the enhancement of biogas productivity without greatly affecting the energy demands of the process [89].…”
Section: The Effect Of Adsorbents and Materials In Accelerating Anaerobic Degradationmentioning
confidence: 99%
“…Following Call and Logan (2008), the energy dissipation in the 10 Ω resistor (W E ) was accounted for in order to determine the actual energy supplied [23]. Gibbs' free energy equation was used to calculate the energy production from CH 4 (∆G CH4 = 890.4 kJ/mol) and H 2 (∆G H2 = 237.1 kJ/mol) [4,24,25].…”
Section: Mec Voltagementioning
confidence: 99%
“…Similarly, the calculated electricity and heat production from a CHP generator was more than double with MEC inclusion compared to AD-only. Previous studies have found the potential electricity production for dairy manure digestion to be between 0.08 and 1.8 kWh/m 3 /d over the entire digestion period [25,50]. By adding an MEC system to just the last 11 days of digestion, the dairy manure electric output went from the lower part of this range to the upper part of this range, while accounting for the electric input needed to operate the MEC.…”
Section: Biogas Utilization In a Fuel Cell Or Combined Heat And Power (Chp) Generatormentioning
confidence: 99%